RESPON KAUM MUDA TERHADAP EKSPRESI PERSATUAN DAN KERAGAMAN DALAM ARSITEKTUR - Barliana, Muhammad Syaom (-)
The objective of this research to inquiry how is the young peopleâs perceptions and responses to the expression of nationalism (unity) and ethnicity (diversity) in the architecture. This research method uses a quantitative approach, qualitative descriptive and was conducted three large cities, namely UPI, UNPAR (Bandung), UI, UNTAR (Jakarta), Udayana (Bali), the architecture student being respondents. The results showed that the perception by students of architecture, form, style, and character of public buildings in the study as a whole to expressed not much strong enough for the aspects of nationality and unity, strong enough for cultural diversity, and hence, these buildings provide enough pride as an Indonesian nation.